Turbulence and order in economic development institutions and economic transformation in Tanzania and Vietnam - Gray, Hazel (Oxford Oxford University Press, 2018)
The terms of debate on the role of institutions in economic development are changing. Stable market institutions, in particular, secure private property rights and democratically accountable governments that uphold the rule of law, are widely seen to be a pre-requisite for economic transformation in low income countries, yet over the last thirty years, economic growth and structural transformation has surged forward in a range of countries where market and state institutions have differed these ideals, as well as from each other. Turbulence and Order in Economic Development studies the role of the state in two such countries, examining the interplay between market liberalization, institutions, and the distribution of power in Tanzania and Vietnam.
Includes bibliographical references (pages 199-227) and index.
Keywords: Economic development--Tanzania.